2019
DOI: 10.1055/a-0809-5408
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of Inert Gas Rebreathing Method to Estimate Cardiac Output at Rest and During Cardiopulmonary Exercise Stress Testing

Abstract: ABStR AC tThe present study evaluated reproducibility of the inert gas rebreathing method to estimate cardiac output at rest and during cardiopulmonary exercise testing. Thirteen healthy subjects (10 males, 3 females, ages 23-32 years) performed maximal graded cardiopulmonary exercise stress test using a cycle ergometer on 2 occasions (Test 1 and Test 2). Participants cycled at 30-watts/ 3-min increments until peak exercise. Hemodynamic variables were assessed at rest and during different exercise intensities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
(53 reference statements)
0
5
0
Order By: Relevance
“…Other studies have shown that exercise promotes cardiomyocyte cell division in response to specific stimuli [2,3,15,16,22]. In preliminary analyses, we found that regular moderate aerobic exercise could induce improvement in cardiac structure and physiological function in wild-type mice and has substantial effects on morphological indices, such as heart size, weight, ventricular wall thickness, and angiogenesis [17].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Other studies have shown that exercise promotes cardiomyocyte cell division in response to specific stimuli [2,3,15,16,22]. In preliminary analyses, we found that regular moderate aerobic exercise could induce improvement in cardiac structure and physiological function in wild-type mice and has substantial effects on morphological indices, such as heart size, weight, ventricular wall thickness, and angiogenesis [17].…”
Section: Discussionmentioning
confidence: 86%
“…Current treatment strategies do not address the problem of myocardial tissue loss and repair. Recent studies indicated that the adult mammalian heart retains regeneration ability in normal conditions or in response to specific stimuli, such as exercise [1][2][3]. However, the optimal cell types for this approach remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…The use of IGR has been shown to produce pulmonary blood flow measurements that are comparable to those obtained by various other methods such as thermodilution, direct Fick, and modified Fick methods during rest as well as graded exercise [46][47][48][49]. Furthermore, this method offers high reproducibility for CO measurements during rest and exercise for both healthy individuals and those with cardiac indications [50,51].…”
Section: Inert Gas Rebreathingmentioning
confidence: 78%
“…The IGR method has high repeatability, reproducibility, and its reliability is not compromised by atrial fibrillation or pulmonary diseases [45,51,55,56,63,76,84]. The IGR method is, therefore, ideally suitable for determining CO in LVAD (Left Ventricular Assist Device) patients at rest and during exercise.…”
Section: Othermentioning
confidence: 99%
See 1 more Smart Citation